Improving Beginning Reading Skills Using Picture Media In First Grade Students At Padahayu Elementary School: - Fauziyah, Iil; Nurani, Riga Zahara; Chandra, Deni (Jurnal Pendidikan Rafflesia, 2025)
The Use of fruit satay  (sabu) image media to improve beginning reading skills of first grade students at SDN Padahayu. This study aims to determine the use of fruit skewer (sabu) image media to improve the beginning reading skills of first-grade students at SDN Padahayu. The research method used is classroom action research, conducted in two cycles, with each cycle consisting of two meetings. The research approach combines both quantitative and qualitative methods. Based on the scores obtained from the observation of student activities in Cycle I, the total score was 40 out of 52, with an average of 3.07 and a percentage of 76.92%. These results fall into the "good" category. The score was achieved because some students were actively engaged during the learning process. In Cycle II, the average score increased to 81.23, which falls into the “very good” category. This shows that the initial reading using fruit satay (sabu) image media implemented at SDN Padahayu Tasikmalaya was carried out well in each cycle.